Bridging divides : the origins of the Beckman Institute at Illinois - Brown, Theodore L. (Theodore Lawrence), 1928- (University of Illinois, 2009)
This book offers a first-hand account of the origins of the Beckman Institute for Advanced Science and Technology, an interdisciplinary research institute at the University of Illinois at Urbana-Champaign devoted to leading-edge research in the physical sciences, computation, engineering, biology, behavior, cognition, and neuroscience. Theodore L. Brown, the Institute's founding director, brings an insider's personal perspective on its conception and its early operations. Brown follows the progress of the Institute's creation, from the initial conceptualization of a large, multidisciplinary institute; through proposal formulation; to the architectural design and actual construction of its state-of-the-art building, completed in 1989 and made possible by the largest gift made to any public university at the time: a $40 million contribution from Illinois alumnus and founder of Beckman Instruments, Inc., Arnold O. Beckman and his wife Mabel M. Beckman.